Meta Analisis Pengaruh Model Creative Problem Solving (CPS) Terhadap Kemampuan Pemecahan Masalah Siswa - Dian Intan Rahmadhani (Institut Agama Islam Negeri Kerinci, 2022)
Meta-analysis Study of the Effect of Creative Problem Solving Models on Students' Problem Solving Ability. This study aims to analyze several other research journals using the meta-analysis method by reviewing or reviewing 10 research journals related to the Effect of Creative Problem Solving Models on Students' Problem Solving Ability. The sample in this study is articles in educational journals that have been published nationally and internationally with certain criteria. The instrument used in this study was a data sheet coding articles or journals. A meta-analysis study was conducted by collecting data by coding 10 journal articles to find the effect size. Based on the article coding data sheet, the overall learning model is able to improve problem solving abilities. This shows that the learning model provides a more effective influence and needs to be applied in learning.